The Influence of work Engagement on Employee Performance: a Scope Review - Yusrina Dwiningsih; M. Taufiq Noor Rokhman; Ratnawati (Journal of Finance and Business Digital, 2023)
Previous literature reviews have explored the relationship of Work Engagement with Employee Performance. The purpose of this scoping review is to map the existing studies that assess the influence of Work Engagement on Employee Performance. The main stages of the scoping review are: (1) identifying research questions; (2) identifying relevant studies; (3) study selection; (4) data charting, and (5) compiling, summarizing, and reporting results. Spanning 10 years (2013-2023), the scoping review results show that most studies recognize that work engagement affects employee performance. However, as claimed by Rahmadalena & Asmanita (2020) that employee engagement has no effect on employee performance.